It is 9*6 minus 7 = 47
6 X 7 = 42.
Product: "The product of 6 and 7 is 42"
Yes it is.
the answer is 7-6=1 7*6=42HEHEH :))
29.
The expression "7 more than the product of 6 and 9" can be written as 6 * 9 + 7. First, you calculate the product of 6 and 9 (6 * 9 = 54), then add 7 to get the final result. Therefore, the expression simplifies to 54 + 7 = 61.
The product of 6 multiplied by 7 is 42.
It is: (28-7) times 6 = 126
42.
6 & 1. 6+1=7 and 6X1=6
It is 9*6 minus 7 = 47
fifty five
(7*7)+6=49+6=55
6 X 7 = 42.
Product: "The product of 6 and 7 is 42"
13